Prehistoric mining at Olympic Dam in arid South Australia. Issue 1 (4th September 2013) - Sullivan, Marjorie; Hughes, Philip; Way, Amy Mosig; Spooner, Nigel
Abstract A site in the Olympic Dam area, recorded during archaeological surveying as a silcrete quarry, was investigated. Hand‐excavated squares and subsequent machine‐excavated trenches revealed an ancient "mine" rather than a simple surface quarry. Blocks of high‐quality silcrete were levered from below the ground surface and many were knapped in the immediate area. Rubble in the pit backfills included large numbers of flakes. Single‐grain optical dates from sediments in the backfilled pits demonstrate that the silcrete "mining" occurred during a short period in the late Holocene.